Gulf Islands, Trinidad (2011)
Colour: Black and white; Style: Landscape; Other: Bordered, Undivided The postcard shows the "Five islands" which is actually a group of six islands that are located west of Port of Spain, the capital of Trinidad, in the Gulf of Paria. They are also known as Las Cortorras. These are Caledonia Island, Craig Island, Lenagen Island, Nelson Island and Pelican Island. The sixth island is Rock Island. Funding for this project has been provided by Mrs. Irma E. Goldstraw.